Utilidad de la goniometría en la evaluación del rango de los movimientos de flexión y extensión de la articulación del codo canino - Mercado M.C. (2008)
Goniometry is a technique widely used in human Kinesiotherapy to evaluate articular angles and demostrated to be a very valuable tool. The authors carried out this work to establish if it is as useful in veterinary medicine to evaluate articular functionality and they chose the elbow joint due to its complexity. 24 canine patients derived to the Physical Therapy Unit of the Veterinary Medicine Teaching Hospital of the Buenos Aires University, Argentine, with a diagnosis of traumatic elbow luxation and its corresponding surgical correction, were selected. During the first physical therapy session data were collected with the aid of a manual goniometer to evaluate bilateral elbow flexion ? extension range of motion, settling down the contralateral forelimb as a normal value for this patient. The same procedure was carried out on the sixteenth session by the same physiotherapist. For all comparisons Statistical analysis Wilcoxon test was used, observing that at the end of the sixteenth session although measurements do not arrive to the normal value of a healthy limb, but a consistent improvement was observed from the first session. We could establish that it supplies an objective criteria to document the progress of the rehabilitation.